Exterior wall putty with strength increased stage by stage and preparation method of exterior wall putty

By using capsule potassium silicate and modified redispersible latex powder in exterior wall putty, putty with a phased increase in strength is designed, which solves the problem of strength increase in exterior wall putty when increasing the bonding strength in the existing technology, and achieves the effect of easy polishing in the early stage of construction and high strength in the later stage.

CN119823607AActive Publication Date: 2025-04-15CARPOLY CHEMICAL GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510202602.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-15
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

When the existing exterior wall putty increases the bonding strength, the overall strength will also increase, resulting in increased polishing difficulty and loss of surface flatness, which cannot meet the needs of construction speed and later strength at the same time.

Method used

Using capsule potassium silicate and modified redispersible latex powder, exterior wall putty with a phased increase in strength is designed by controlling the cement hydration reaction speed and viscosity performance. The putty has a low strength in the early stage of construction, which is easy to polish and smooth; then the strength gradually increases, making it suitable for subsequent coating construction; it reaches high strength after 28 days to ensure the safety of the exterior wall coating.

Benefits of technology

It achieves easy to polish and smooth in the early stage of construction, and has high strength in the later stage, meeting the dual needs of early construction speed and later strength of building exterior wall putty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823607A_ABST
    Figure CN119823607A_ABST
Patent Text Reader

Abstract

The invention provides exterior wall putty with strength increased in stages. The exterior wall putty with the strength increased in the staged mode is prepared from, by mass, 1.5%-2.5% of capsule type potassium silicate, 1.5%-2.5% of modified redispersible latex powder, 30%-40% of Portland cement, 35%-45% of sand, 20%-30% of ground calcium carbonate, 0.3%-0.5% of cellulose ether, 0.03%-0.06% of starch ether and 0.05%-0.15% of sodium gluconate. Sodium gluconate and capsule type potassium silicate are added into putty of a Portland cement system, sodium gluconate plays a role in retarding cement hydration after being dissolved, the concentration of calcium ions in a reaction product is gradually increased along with slow cement hydration reaction, meanwhile, outer capsules of potassium silicate are gradually dissolved, and the calcium ions in the cement hydration reaction product are gradually reduced. Potassium silicate reacts with calcium ions to generate a more stable insoluble compound, so that the hydration reaction speed and the overall strength of the cement are improved, and the reaction is performed until the potassium silicate is completely consumed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dry-mix mortar building materials, and mainly relates to an exterior wall putty with staged strength increase and a preparation method thereof. Background Art

[0002] Cracking, bulging, and peeling of exterior wall coatings are common, seriously impacting the overall aesthetics, safety, and service life of a building. Exterior wall putty is a key contributing factor. As the connecting material between the base layer and the paint, exterior wall putty requires both strong adhesion to the base layer and excellent surface smoothness. However, increasing the putty's bond strength also increases overall strength, making polishing more difficult and compromising surface smoothness. This creates a conflict between the two.

[0003] Furthermore, currently, super-high-rise buildings are primarily constructed using climbing scaffolding, which typically takes 4-6 days to raise one floor. To save costs, exterior wall putty application is carried out in tandem with the progress of the climbing scaffolding, meaning each layer of exterior wall putty takes 4-6 days to scrape and polish. Therefore, within 1-3 days of application, the putty should exhibit excellent sandability, saving time and labor. Furthermore, it should maintain high strength later on, ensuring adhesion to the base layer and the paint's adhesion to the putty.

[0004] In order to meet the above coating requirements, the mainstream adjustment idea is to balance the addition amount of silicate cement and latex powder in the putty formula so that the polishability and strength of the putty are at an intermediate value. However, none of them meet the most ideal requirements and do not fundamentally solve the problem.

[0005] In summary, it is necessary to develop a new technical solution to solve the defects and shortcomings in the existing technology. Summary of the Invention

[0006] The purpose of the present invention is to provide an exterior wall putty with a staged strength increase. The strength increases slowly within 3 days of construction, which is conducive to surface polishing. The strength increases rapidly within 3-7 days, which is conducive to the construction of subsequent coatings. The strength increases slowly within 7-28 days, and the final strength is high, thereby ensuring the safety of the exterior wall coating.

[0007] One object of the present invention is to provide an exterior wall putty with a gradually increasing strength, wherein the exterior wall putty with a gradually increasing strength comprises the following components in mass fraction:

[0008]

[0009]

[0010] in,

[0011] The capsule-type potassium silicate is potassium silicate coated with polyvinyl alcohol;

[0012] The modified redispersible latex powder is obtained by reacting vinyl acetate-ethylene-acrylic acid copolymer with tannic acid.

[0013] Furthermore, the sand is river sand or machine-made sand in the range of 40-140 mesh.

[0014] Furthermore, the heavy calcium carbonate is calcium carbonate powder in the range of 150-325 mesh.

[0015] Furthermore, the cellulose ether is selected from one or more of methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose or hydroxyethyl methyl cellulose.

[0016] Furthermore, the starch ether is potato modified starch.

[0017] Another object of the present invention is to provide a method for preparing the above-mentioned exterior wall putty with gradually increasing strength, comprising the following steps:

[0018] S1, mixing polyvinyl alcohol with water, heating and stirring, adding a defoamer, stirring to obtain a polyvinyl alcohol protective colloid; mixing potassium silicate with water, filtering to obtain a potassium silicate solution;

[0019] S2. Blending the polyvinyl alcohol protective colloid and the potassium silicate solution, heating and stirring, adding a defoamer, and stirring to obtain a mixed dispersion; spray-drying the mixed dispersion to obtain a mixed powder, and sieving to obtain encapsulated potassium silicate;

[0020] S3, blending vinyl acetate and acrylic acid, evacuating the mixture and introducing ethylene, then adding an initiator, heating and stirring the mixture to react, to obtain a vinyl acetate-ethylene-acrylic acid copolymer;

[0021] S4, blending the vinyl acetate-ethylene-acrylic acid copolymer and tannic acid, then adding a catalyst, heating and reacting to obtain a modified redispersible latex powder;

[0022] S5. Blending the encapsulated potassium silicate, sodium gluconate and heavy calcium carbonate, stirring evenly to obtain a heavy calcium carbonate premix;

[0023] S6. Blend the heavy calcium premix, Portland cement, sand, modified redispersible latex powder, cellulose ether and starch ether, and stir evenly to obtain an exterior wall putty with gradually increased strength.

[0024] Furthermore, when in use, the exterior wall putty with gradually increasing strength is mixed with water in a weight ratio of 1:(0.3±0.01) and stirred into a uniform paste without particles.

[0025] Furthermore, in step S1, the mass ratio of the polyvinyl alcohol to potassium silicate is 1:(6-9).

[0026] Furthermore, in step S3, the mass ratio of vinyl acetate, acrylic acid and ethylene is (0.5-1.5):(1-3):1.

[0027] Furthermore, in step S4, the mass ratio of the vinyl acetate-ethylene-acrylic acid copolymer to tannic acid is 1:(0.5-1.5).

[0028] Furthermore, in step S1, the heating temperature is 70-90°C.

[0029] Furthermore, in step S2, the heating temperature is 80-100°C.

[0030] Furthermore, in step S3, the heating temperature is 80-100°C.

[0031] Furthermore, in step S4, the heating temperature is 100-120°C.

[0032] The present invention has the following beneficial effects:

[0033] (1) The present invention adds sodium gluconate and capsule-type potassium silicate to the putty of the silicate cement system. After the sodium gluconate dissolves, it has a blocking effect on the cement hydration and reduces the hydration rate. As the cement hydration reaction slowly proceeds, the concentration of calcium ions in the reaction product gradually increases. At the same time, the potassium silicate outer capsule gradually dissolves, and the potassium silicate reacts with the calcium ions to form a more stable insoluble compound, thereby increasing the cement hydration reaction rate and overall strength. The reaction continues until the potassium silicate is completely consumed. The macroscopic performance of the exterior wall putty is that the strength is low on the 3rd day, the strength gradually recovers on the 7th day, and the strength is high on the 28th day, which meets the requirements of easy polishing in the early stage and high strength in the later stage of the building exterior wall putty.

[0034] (2) The modified redispersible latex powder of the present invention is obtained by the reaction of vinyl acetate-ethylene-acrylic acid copolymer and tannic acid, and a large number of active groups such as hydroxyl groups are introduced, which can effectively enhance its viscosity and improve the bonding strength of putty; at the same time, the modified redispersible latex powder has good compatibility with encapsulated potassium silicate, and the hydroxyl groups on the surfaces of the two can interact with each other, thereby improving the adhesion of putty to the substrate and enhancing the performance of putty.

[0035] Figures in the specification

[0036] Figure 1 The bonding strength test results of Example 1 and Comparative Examples 1-5 at 3, 7, 14, 21 and 28 days are shown. DETAILED DESCRIPTION

[0037] In order to more clearly illustrate the technical solution of the present invention, the following examples are given. Unless otherwise stated, the raw materials, reactions and post-processing methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0038] The terms "preferred," "preferably," "more preferred," and the like, used herein, refer to embodiments of the invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, nor is it intended to exclude other embodiments from the scope of the invention.

[0039] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers expressing, for example, quantities of ingredients used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending upon the desired properties to be obtained by the present invention.

[0040] The following raw materials are used in the examples and comparative examples of the present invention:

[0041] The silicate cement is PO 42.5 gray cement.

[0042] The sand is river sand in the range of 40-140 mesh.

[0043] Heavy calcium carbonate is calcium carbonate powder in the range of 150-325 mesh.

[0044] The cellulose ether is hydroxypropyl methylcellulose with a viscosity of 75000-100000 mPa.s.

[0045] Starch ether is potato modified starch with a viscosity of 400-1200 mPa.s.

[0046] Sodium gluconate is a crystalline powder with an effective content of ≥97%.

[0047] The polyvinyl alcohol model is PVA-2488.

[0048] The modulus of instant potassium silicate is 2.3-2.5.

[0049] The defoaming agent is an organosilicon defoaming agent with the brand name F210, purchased from Shanghai Guben Industrial Co., Ltd.

[0050] The release agent is 4000 mesh calcined kaolin with the brand name Baixue 80, purchased from Tangshan Madison Kaolin Co., Ltd.

[0051] Example 1

[0052] An exterior wall putty with gradually increasing strength, comprising the following components by mass fraction:

[0053]

[0054] The preparation method of the above-mentioned exterior wall putty with gradually increasing strength comprises the following steps:

[0055] S1. Pour 960 kg of water into the reactor, heat it to 40 ° C, add 40 kg of polyvinyl alcohol, continue to heat it to 80 ° C, stir for 30 min, add 1 kg of defoamer, continue stirring for 10 min to obtain polyvinyl alcohol protective colloid, cool it to 30 ° C, and keep it warm for later use; dissolve 300 kg of instant potassium silicate in 700 kg of water, and filter it through a 160 mesh filter to obtain a potassium silicate solution;

[0056] S2, start the reactor, stir and heat to 90 ° C, add the polyvinyl alcohol protective colloid and potassium silicate solution into the reactor, mix and stir for 30 min, add 1 kg defoamer, and continue stirring for 10 min to obtain a mixed dispersion; the mixed dispersion is pumped to a drying tower, the tower inlet temperature is controlled at 140 ± 5 ° C, the mixed dispersion is uniformly atomized into the tower by a spray device, and a release agent is added to the air flow. The atomized micro-droplets are rapidly evaporated and dried to form a gas-solid mixture, which is derived from the air outlet at the bottom of the tower and collected to obtain a mixed powder; the mixed powder is passed through a 90-mesh sieve to collect particles ≥90 mesh to obtain capsule-type potassium silicate;

[0057] S3. Using water as a solvent, vinyl acetate and acrylic acid were blended, the mixture was evacuated and ethylene was introduced (vinyl acetate: acrylic acid: ethylene = 1:1:1, m / m) and the pressure was increased to 5 MPa. Then, 1 wt% of tert-butyl hydroperoxide was added, and the mixture was heated and stirred at 85° C. for 5 h. The mixture was filtered, washed, and dried to obtain a vinyl acetate-ethylene-acrylic acid copolymer.

[0058] S4. Using dimethyl sulfoxide as a solvent, the vinyl acetate-ethylene-acrylic acid copolymer and tannic acid are blended, and p-toluenesulfonic acid is added (vinyl acetate-ethylene-acrylic acid copolymer: tannic acid: p-toluenesulfonic acid = 1:1:0.3, m / m / m). The mixture is reacted at 110° C. for 12 h, filtered, washed, and dried to obtain a modified redispersible latex powder.

[0059] S5. Blend the encapsulated potassium silicate, sodium gluconate and heavy calcium carbonate according to the above mass fractions, stir evenly, and obtain a heavy calcium carbonate premix;

[0060] S6. The modified redispersible latex powder, heavy calcium premix, Portland cement, sand, cellulose ether and starch ether are blended and stirred evenly to obtain an exterior wall putty with gradually increased strength.

[0061] Example 2

[0062] An exterior wall putty with gradually increasing strength, comprising the following components by mass fraction:

[0063]

[0064] The preparation method of the above-mentioned exterior wall putty with phased strength increase is the same as that in Example 1.

[0065] Example 3

[0066] An exterior wall putty with gradually increasing strength, comprising the following components by mass fraction:

[0067]

[0068]

[0069] The preparation method of the above-mentioned exterior wall putty with phased strength increase is the same as that in Example 1.

[0070] Comparative Example 1

[0071] A comparative example of an exterior wall putty with gradually increasing strength. The difference between this comparative example and Example 1 is that step S1-2 is not performed, and in step S5, the encapsulated potassium silicate is replaced by a physical mixture of polyvinyl alcohol and instant potassium silicate, and the amount thereof is the same as that in step S1. The remaining ingredients and preparation method are the same as those in Example 1.

[0072] Comparative Example 2

[0073] A comparative example of an exterior wall putty with gradually increasing strength. The comparative example differs from Example 1 in that the mass of the encapsulated potassium silicate is replaced by heavy calcium carbonate, and the remaining ingredients and preparation method are the same as those of Example 1.

[0074] Comparative Example 3

[0075] A comparative example of an exterior wall putty with gradually increasing strength. The comparative example differs from Example 1 in that the sodium gluconate is replaced by heavy calcium carbonate, and the remaining ingredients and preparation method are the same as those of Example 1.

[0076] Comparative Example 4

[0077] A comparative example of an exterior wall putty with gradually increasing strength. The comparative example differs from Example 1 in that the capsule-type potassium silicate and sodium gluconate are replaced by heavy calcium carbonate, and the remaining ingredients and preparation method are the same as those of Example 1.

[0078] Comparative Example 5

[0079] A comparative example of an exterior wall putty with gradually increasing strength. The difference between this comparative example and Example 1 is that the modified redispersible latex powder is replaced by a physical mixture of vinyl acetate-ethylene-acrylic acid copolymer and tannic acid, and the amount thereof is the same as in steps S3 and S4. The remaining ingredients and preparation method are the same as in Example 1.

[0080] Test Case

[0081] 1. Bond strength test

[0082] Test method: According to the bonding strength test method in JG / T 157-2009 "Putty for Building Exterior Walls", the bonding strength of Example 1 and Comparative Examples 1-5 at 3, 7, 14, 21 and 28 days were tested respectively.

[0083] The test results are as follows Figure 1 and as shown in Table 1.

[0084] Table 1 Bond strength test results of Example 1 and Comparative Examples 1-5

[0085]

[0086]

[0087] 2. Polishability test

[0088] The polishing property of putty is evaluated by the powder loss rate. The higher the powder loss rate, the easier it is to polish, and vice versa.

[0089] The polishability test of putty coating is carried out according to the following method:

[0090] (1) Test substrate: Asbestos-free cement flat plate with dimensions of 70 mm × 150 mm;

[0091] (2) Film making mold: outer frame size 70mm×150mm, inner frame size 60mm×140mm, thickness 1mm, stainless steel or acrylic molding frame;

[0092] (3) Coating preparation: Place the mold flat on a cement plate with the edges aligned, pour the mixed material into the mold, and use a steel scraper to compact and flatten the material. The coating should be flat, dense, without defects and bubbles. Prepare 3 samples for each test piece and place them in a curing room for 3 days.

[0093] (4) Curing conditions: temperature 25 ± 2 °C, relative humidity 50 ± 5%;

[0094] (5) Polishing test: Use a cube-shaped pressing block with a side length of 60 mm and a weight of 500 g, paste 240-grit sandpaper on one side, place the side with sandpaper flat on the putty coating, align the edges on both sides, and drag the pressing block back and forth. The single-stroke dragging distance is 80 mm. After dragging back and forth 10 times, use a wool brush to clean the dust on the test block.

[0095] (6) Calculation method: Before making the sample, weigh the non-asbestos cement plate, record it as M0; after the test block is made and cured for 3 days, weigh it, record it as M1; after the test block is polished and cleaned of dust, weigh it, record it as M2;

[0096]

[0097] (7) For each test sample, three samples are tested and the average of the three values ​​is taken. The difference between the average value and any single value cannot exceed 20%, otherwise it is considered invalid and should be retested;

[0098] The polishing test results of Example 1 and Comparative Examples 1-5, and the powder loss rate results are shown in Table 2.

[0099] Table 2 Powder loss rate test results of Example 1 and Comparative Examples 1-5

[0100] project Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Fan loss rate% 5.93 2.16 6.02 1.97 3.37 5.87

[0101] From the above test results, it can be seen that the grinding powder loss rates of Example 1 and Comparative Example 2 are similar, and are significantly higher than those of Comparative Example 1, Comparative Example 3 and Comparative Example 4. Example 1 has better grindability; since the potassium silicate in Comparative Example 1 is not coated, it will quickly react with the cement hydration product after dissolving in water to improve the early strength, but at the same time it is affected by the retarding effect of sodium gluconate, so the powder loss rate is significantly lower than that of Example 1 and higher than that of Comparative Example 3.

[0102] Figure 1 The bonding strength test results of Example 1 and Comparative Examples 1-5 at 3, 7, 14, 21 and 28 days are shown; Figure 1 According to the middle curve and the data in Table 1, the bonding strength of Example 1, Comparative Example 1 and Comparative Example 3 is significantly higher than that of Comparative Example 2 and Comparative Example 4 at 28 days.

[0103] comprehensive Figure 1 , Table 1 and Table 2, the present invention has excellent polishability and later bonding strength 3 days after construction, meeting the coating requirements in practical applications.

[0104] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

[0105] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. An exterior wall putty with a staged increase in strength, characterized in that: The exterior wall putty with a phased increase in strength includes the following components by mass fraction: in, The capsule-type potassium silicate is potassium silicate coated with polyvinyl alcohol; The modified redispersible latex powder is obtained by reacting vinyl acetate-ethylene-acrylic acid copolymer with tannic acid.

2. The exterior wall putty with a stepwise increase in strength according to claim 1, characterized in that: The cellulose ether is selected from one or more of methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose or hydroxyethyl methyl cellulose.

3. The exterior wall putty with a stepwise increase in strength according to claim 1, characterized in that: The starch ether is potato modified starch.

4. The method for preparing the exterior wall putty with the staged strength increase according to claims 1-3, characterized in that: The steps include: S1, mixing polyvinyl alcohol with water, heating and stirring, adding a defoamer, stirring, and obtaining a polyvinyl alcohol protective colloid; mixing potassium silicate with water, filtering, and obtaining a potassium silicate solution; S2, blending the polyvinyl alcohol protective colloid and the potassium silicate solution, heating and stirring, adding a defoamer, stirring, and obtaining a mixed dispersion; spray drying the mixed dispersion to obtain a mixed powder, sieving, and obtaining capsule-type potassium silicate; S3, blending vinyl acetate and acrylic acid, evacuating the mixture and introducing ethylene, then adding an initiator, heating and stirring the mixture to react, and obtaining a vinyl acetate-ethylene-acrylic acid copolymer; S4, blending the vinyl acetate-ethylene-acrylic acid copolymer and tannic acid, then adding a catalyst, heating for reaction, and obtaining a modified redispersible latex powder; S5, blending the capsule-type potassium silicate, sodium gluconate and heavy calcium carbonate, stirring evenly to obtain a heavy calcium carbonate premix; S6. Blending the heavy calcium premix, silicate cement, sand, modified redispersible latex powder, cellulose ether and starch ether, and stirring evenly to obtain an exterior wall putty with a phased increase in strength.

5. The method for preparing the exterior wall putty with the staged increase in strength according to claim 4, characterized in that: In step S1, the mass ratio of polyvinyl alcohol to potassium silicate is 1:(6-9).

6. The method for preparing the exterior wall putty with the strength increasing in stages according to claim 4, characterized in that: In step S3, the mass ratio of vinyl acetate, acrylic acid and ethylene is (0.5-1.5):(1-3):

1.

7. The method for preparing the exterior wall putty with the strength increasing in stages according to claim 4, characterized in that: In step S4, the mass ratio of the vinyl acetate-ethylene-acrylic acid copolymer to tannic acid is 1:(0.5-1.5).

8. The method for preparing the exterior wall putty with the strength increasing in stages according to claim 4, characterized in that: In step S1, the heating temperature is 70-90°C.

9. The method for preparing the exterior wall putty with the strength increasing in stages according to claim 4, characterized in that: In step S2, the heating temperature is 80-100°C.

10. The method for preparing the exterior wall putty with gradually increasing strength according to claim 4, characterized in that: In step S3, the heating temperature is 80-100°C.

Citation Information

Patent Citations

  • Microencapsulation method of concrete water-based repair agent

    CN103613318A

  • Non-redispersible latex powder and application thereof

    CN104098814A

  • Slow release type polyphosphate curing agent, preparation method and application thereof in preparation of sodium silicate curing product

    CN106966628A

  • Environment-friendly type building dry powder coating and preparation method thereof

    CN107286759A

  • Waterproof flexible material for external insulating wall space

    CN107446404A